1996
DOI: 10.1037/0096-1523.22.3.615
|View full text |Cite
|
Sign up to set email alerts
|

Testing models of decision making using confidence ratings in classification.

Abstract: Classification implies decision making (or response selection) of some kind. Studying the decision process using a traditional signal detection theory analysis is difficult for two reasons: (a) The model makes a strong assumption about the encoding process (normal noise), and (b) the two most popular decision models, optimal and distance-from-criterion models, can mimic each other's predictions about performance level. In this article, the authors show that by analyzing certain distributional properties of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(110 citation statements)
references
References 12 publications
4
104
2
Order By: Relevance
“…Calculations were also performed using small samples (10 -50) resampled from experimental data sets. In these data, s L and s H were very similar (e.g., lines of length 6.75 and 6.9 cm, with n 5 6.6 cm), and the two conditions were presented in intermingled short blocks in 2-h sessions with well-practiced subjects (Balakrishnan & Ratcliff, 1996). The previous finding was supported (Balakrishnan, 1998b, Table 3).…”
Section: Balakrishnan's (1998b) New Measure Of Sensitivity S9supporting
confidence: 73%
“…Calculations were also performed using small samples (10 -50) resampled from experimental data sets. In these data, s L and s H were very similar (e.g., lines of length 6.75 and 6.9 cm, with n 5 6.6 cm), and the two conditions were presented in intermingled short blocks in 2-h sessions with well-practiced subjects (Balakrishnan & Ratcliff, 1996). The previous finding was supported (Balakrishnan, 1998b, Table 3).…”
Section: Balakrishnan's (1998b) New Measure Of Sensitivity S9supporting
confidence: 73%
“…Consequently, the fundamentally similar nature of absolute magnitude estimations and the confidence estimates generated by the new procedure may point to a similar insensitivity to context effects for the confidence procedure. Finally, Balakrishnan and Ratcliff (1996) reported little evidence of context effects for a task requiring participants to use confidence ratings to discriminate between and categorize lines of varying lengths. Thus, the extant literature makes no clear predictions about the likelihood of observing context effects for the new procedure.…”
Section: Methodsmentioning
confidence: 99%
“…We refer to this model, which is illustrated in the top panel of Figure 3, as the lockstep model because all of the criteria move together. This model has also been referred to as the distance from criterion model because the position of a particular confidence criterion is always a fixed distance from the old-new decision criterion (Balakrishnan & Ratcliff, 1996). The lockstep model is both computationally simple and intuitively plausible.…”
Section: Lockstep Modelmentioning
confidence: 99%
“…Balakrishnan and Ratcliff (1996) recently found that for a strength manipulation the lockstep model (which they termed the "distance from criterion" model) provided a better account of their data than the likelihood ratio model. Their method of analysis differed considerably from the one used here.…”
Section: Prior Research On Strength and Confidencementioning
confidence: 99%
See 1 more Smart Citation